Hukum Menjawab Gejala Sosial Masyarakat - Muhammad Al Faruq (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
The development of an increasingly advanced world accompanied by the era ofglobalization and the rapid development of science and technology in several areasof people's lives has brought great influence, including on legal issues. Islamicsociety as an inseparable part of the world, cannot escape from problems thatconcern the legal position of an issue. New problems that arise among Muslimssometimes have unclear legal status in the two main sources of law, namely theQur'an and hadith, requiring the Ulama to provide quick and appropriate solutions and answers so that Islamic law becomes responsive and dynamic. This is where the strategic position of ijtihad as an instrument for conducting